2.5k views
3 votes
What is the product of a+3 and −2a2+15a+6b2?

User Htaccess
by
6.4k points

1 Answer

3 votes

For this case we must find the product of the following expression:


(a + 3) (- 2a ^ 2 + 15a + 6b ^ 2)

We apply distributive property term to term:


(a + 3) (- 2a ^ 2 + 15a + 6b ^ 2) =\\-2a ^ 2 * a + 15a * a + 6b ^ 2 * a-6a ^ 2 + 45a + 18b ^ 2 =\\-2a ^ 3 + 15a ^ 2 + 6ab ^ 2-6a ^ 2 + 45a + 18b ^ 2=

We add similar terms:


-2a ^ 3 + (15-6) a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2 =\\-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2 =

Finally, the expression is as:


-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2

Answeer:


-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2

User Leonheess
by
7.4k points